Europa, Europa : Das Jahrhundert der Avantgarde in Mittel- und Osteuropa. - Awerinzew, Sergei; Bakshtein, Joseph; Basner, Elena; Beke, László; Bessonova, Marina; Bois, Yve-Alain; Borowski, Wieslaw; Brockhaus, Christoph; Czartoryska, Urszula; Daniels, Dieter; Davies, Norman; Deecke, Thomas; et al. (Bonn : Stiftung Kunst und Kultur des Landes Nordrhein-Westfalen, 1994)
Band I : Abakanowicz, Magdalena ; Abramovic, Marina ; Adler, Jankel ; Al'tman, Natan ; Altorjal, Sandor ; Amos, Imre ; Archipenko, Aleksandr ; Balcytis, Vytautas ; Balka, Miroslaw ; Baranov-Rossiné, Vladimir ; Barany, Nandor ; Barta, Zsolt-Peter ; Beksinki, Zdzislaw ; Beothy, Etienne ; Beres, Jerzy ; Bernik, Janez ; Bódy, Gabor ; Bor, Vane ; Bortnyik, Sándor ; Bostik, Vaclav ; Brancusi, Constantin ; Brassaï, Henri ; Brauner, Victor ; Bruskin, Grisha ; Brzeski, Janusz Maria ; Brzozowski, Tadeusz ; Budvytis, Alfonsas ; Buic, Jagoda ; Bulatov, Erik ; Capek, Josef ; Chagall, Marc ; Christo ; Ciecierski, Tomasz ; Ciurlionis, Mikalojus ; Dimitrijevic, Braco ; Divis, Alén ; Dlubak, Zbigniew ; Drtikol, Frantisek ; Dunikowski, Xawery ; Dzamonja, Dusan ; Ender, Boris ; Fijalkowski, Stanislaw ; Filla, Emil ; Filonov, Pavel ; Funke, Jaromir ; Gabo, Naum ; Gerlovin, Valeriy ; Gerlovina, Rimma ; Gierowski, Stefan ; Gliha, Oton ; Goncarova, Natal'ja ; Gostomski, Zbigniew ; Grobman, Michail ; Grygar, Milan ; Grzinic, Marina ; Gulácsy, Lajos ; Guro, Elena ; Gutfreund, Otto ; Hajas, Tibor ; Hák, Miroslav ; Hasior, Wladyslaw ; Heisler, Jindrich ; Hencze, Tamas ; Hiller, Karol ; Infante, Francisco ; Inganson, Karl ; Jacobi, Ritzi & Peter ; Jakopic, Rihard ; Jakoviev, Vladimir ; Janco, Marcel ; Jankovic, Jozef ; Jarema, Maria ; Jetelova, Magdalena ; John, Jiri ; Kabakov, Ilya ; Kandinskij, Vasilij ; Kantor, Tadeusz ; Kassak, Lajos ; Kemeny, Zoltan ; Kerekes, Gabór ; Kertesz, André ; Kiraly, Iosif ; Klucis, Gustav ; Knifer, Julije ; Knizak, Milan ; Kobro, Katarzyna ; Kokolia, Vladimir ; Kolar, Jiri ; Kolarová, Bela ; Komar & Melamid ; Konenkov, Sergej ; Kosztka, Tivadar Csontváry ; Koudelka, Josef ; Kovacs, Attila ; Kowalski, Piotr ; Kozlowski, Jaroslaw ; Krasinksi, Edward ; etc.
Band II : Abuladze, Tengiz ; Alabjan, Karo ; Alejchem, Scholem ; Bachmann, Gábor ; Baetge, Kurt ; Bahna, Ján ; Barnet, Boris ; Bódy, Gabor ; Borowczyk, Walerian ; Brasovan, Dragisa ; Büchner, Georg ; Cechov, Anton ; Chesterton, Gilbert K. ; Chlebnikov, Velimir ; Chmielewski, Konrad ; Chochol, Josef ; Chuciev, Marlen ; Chytilová, Vera ; Creangä, Horia ; Crommelynck, Fernand ; Denisov, Edison ; Dobai, János ; Dovzenko, Aleksandr ; Duskin, Aleksej ; Ejzenstejn, Sergej ; Fábri, Zoltán ; Forman, Milos ; German, Aleksej ; Göde, András ; Golyscheff, Jefim ; Gotovac, Tomislav ; Gozzi, Carlo ; Gubajdulina, Sofija ; Hába, Alois ; Hackenschmied, Alexander ; Havel, Václav ; Hempel, Stanislaw ; Hoffmann, E.T.A. ; Honzl, Jindrich ; Hrusa, Petr ; Iofan, Boris ; Janácek, Leos ; Jasinski, Krzystof ; Jovanovic, Dusan ; Kaiser, Georg ; Kalatozov, Michail ; Kantor, Tadeusz ; Karr, Alfred ; Kassak, Lajos ; Kempf, Davorin ; Kiéslowski, Krzysztof ; Kobro, Katarzyna ; Korunovic, Momir ; Kovacic, Viktor ; Kozincev, Grigorij ; Krejcar, Jaromir ; Kulesov, Lev ; Kurtág, György ; Kutavicius, Bronius ; Lenica, Jan ; Leonidov, Ivan ; Ligeti, György ; Linek, Jan ; Lisickij, El' ; Lourié, Arthur ; Lutolawski, Witold ; Madzik, Leszek ; Majakovskij, Vladimir ; Makovecz, Imre ; Malevich, Kasimir ; Marbé, Myriam ; Marcu, Duiliu ; Matjusin, Michail ; Mejerchol'd, Vsevolod ; Mel'nikov, Konstantin ; Menzel, Jiri ; Mickiewicz, Adam ; Milunic, Vlado ; Moholy-Nagy, Laszlo ; Molnár, Farkas ; Munk, Andrzej ; Murzin, Evgenij ; Nagy, Tamás ; Nemec, Martin ; Niemczyk, Stanislaw ; Nowicki, Maciej ; Obuchov, Nikolaj ; Paál, Istvan ; Paradzanov, Sergej ; Pärt, Arvo ; Patraszewska, Barbara ; Perec, Isaak ; Petrovic, Aleksandar ; Pieta, Andrzej ; Pinos, Alois ; Plecnik, Joze ; Polanski, Roman ; etc.
Band III : Abramovic, Marina ; Archipenko, Aleksandr ; Bill, Max ; Brauner, Victor ; Chagall, Marc ; Dimitrijevic, Braco ; Gabo, Naum ; IRWIN ; Kabakov, Ilya ; Mucha, Alfons ; Opalka, Roman ; Oroschakoff, Haralampi G. ; Sima, Josef ; Vajda, Lajos ; Vrubel, Michail
Band IV : Abakanowicz, Magdalena ; Abramovic, Marina ; Abuladze, Tengiz E. ; Adler, Jankel ; Ady, Endre ; Ajgi, Gennadij N. ; Al'tman, Natan I. ; Alejnikov, Gleb ; Alejnikov, Igor ; Altorjal, Sandor ; Amos, Imre ; Anisfel'd, Boris I. ; Archipenko, Aleksandr ; Askoldov, Aleksandr Ja. ; Bacewicz, Grazyna ; Bacovia, George ; Baird, Tadeusz ; Bakst, Leon ; Balcytis, Vytautas ; Balka, Miroslaw ; Baranov-Bossiné, Vladimir D. ; Barany, Nandor ; Barnet, Boris V. ; Barta, Zsolt-Peter ; Bartók, Béla ; Bauer, Evgenij F. ; Beban, Breda ; Beksinski, Zdzislaw ; Benois, Alexandre ; Bens, Adolf ; Beothy, Etienne ; Beres, Jerzy ; Berg, Josef ; Berlewi, Henryk ; Bernik, Janez ; Bialoszewski, Miron ; Bilek, Frantisek ; Blaga, Lucian ; Blecher, Marcel ; Bloch, Augustyn ; Blok, Aleksandr A. ; Bódy, Gabor ; Bor, Vane Zivadinovic ; Borowczyk, Walerian ; Bortnyik, Sándor ; Bostik, Vaclav ; Brancusi, Constantin ; Brasovan, Dragisa ; Brassaï ; Bratescu, Greta ; Brauner, Victor ; Brodsky, Joseph A. ; Brukalski, Stanislaw ; Bruskin, Grisha ; Brzeski, Janusz Maria ; Brzozowski, Tadeusz ; Budvytis, Alfonsas ; Buic, Jagoda ; Bulatov, Erik V. ; Burian, Emil Frantisek ; Busoni, Ferrucio ; Capek, Josef ; Capek, Karel ; Cechanovskij, Michail M. ; Cemy, Frantisek Maria ; Cernichov, Jakov G. ; Chacatur'jan, Aram I. ; Chagall, Marc ; Chidekel', Lazar M. ; Chlebnikov, Velimir ; Chocol, Josef ; Christo & Jeanne-Claude ; Chwistek, Leon ; Chytilová, Vera ; Ciecierski, Tomasz ; Ciulei, Liviu ; Ciurlionis, Mikalojus K. ; Creangä, Horia ; Daneliuc, Mircea ; Denisov, Edison V. ; Déry, Tibor ; Detoni, Dubravko ; Dimitrijevic, Braco ; Dinescu, Violeta ; Divis, Alén ; Djulgerov, Georgi ; Dlubak, Zbigniew ; Dmitriev, Vladimir V. ; Dobrovic, Nikola ; Dovsenko, Aleksandr P. ; Drtikol, Frantisek ; etc.
Duits
boek
Keywords: Midden-Europa; Oost-Europa